Eksplorasi Keterlaksanaan Model Problem-Based Learning pada Pembelajaran Biologi Kelas XI di SMA Negeri 6 Medan - Putri Yasmin; Widya Arwita (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
This study aims to examine the implementation of the Problem-Based Learning (PBL) model in Grade XI biology learning at SMA Negeri 6 Medan. This study employed a qualitative case study approach involving one biology teacher and students of Class XI Merdeka 1. The focus was on the application of PBL syntax in classroom practices. Data were collected through document analysis, classroom observations, and questionnaires administered to both the teacher and students. Data validity was ensured through technique and source triangulation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that PBL was systematically planned through teaching modules aligned with the Merdeka Curriculum. In practice, learning was generally implemented as planned and received positive responses, particularly in individual and group investigation activities, although several aspects were not yet fully optimal. Students demonstrated active participation and collaboration. However, challenges were identified in scientific communication skills, reflective activities, and assessment practices that were not fully aligned with the initial planning, which may limit the development of higher-order thinking skills. Overall, PBL shows potential to support students’ critical thinking and collaboration, although the findings are limited to this context and should not be generalized.